Genetic alterations in myeloid sarcoma among acute myeloid leukemia patients: insights from 37 cohort studies and a meta-analysis - Untaaveesup, Suvijak; Trithiphen, Sasinipa; Kulchutisin, Kamolchanok; Rungjirajittranon, Tarinee; Leelakanok, Nattawut; Panyoy, Sujitra; Kaokunakorn, Thanapon; Owattanapanich, Weerapat (Frontiers in Oncology, 2024)
Introduction Variations in mutation rates among acute myeloid leukemia (AML) patients with myeloid sarcoma (MS) underscore the need for a thorough examination. This meta-analysis was conducted to fill the information gap concerning mutation frequencies in AML patients presenting with MS. Materials and methods This study included retrospective and prospective cohorts. It examined genetic alterations in AML patients with and without MS across all age groups. The search strategy employed terms such as “acute myeloid leukemia,” “extramedullary,” “granulocytic sarcoma,” “myeloid sarcoma,” and “leukemic cutis” in the EMBASE, MEDLINE, and Scopus databases. Excluded from the study were reviews, case reports, and case series with fewer than 10 cases. Statistical analyses were performed with Review Manager 5.4 software. Results The primary analysis incorporated data from 37 cohorts involving 5646 diagnosed AML patients and revealed a 17.42% incidence of MS. The most prevalent mutation among AML patients with MS was FLT3-ITD, with a pooled prevalence of 17.50% (95% CI 12.60% to 22.50%; I2 82.48%). The dominant fusion gene was RUNX1::RUNX1T1, displaying a pooled prevalence of 28.10% (95% CI 15.10% to 41.20%; I2 96.39%). In comparison, no significant intergroup differences were observed for NPM1, FLT3-ITD, KIT, and IDH2 mutations. Interestingly, the CEBPA mutation exhibited protective effects for MS patients, with an odds ratio of 0.51 (95% CI 0.32 to 0.81; I2 0%). Conversely, the NRAS mutation was associated with an increased risk of MS development, with an odds ratio of 5.07 (95% CI 1.87 to 13.73; I2 0%). Conclusion This meta-analysis sheds light on the prevalence of genetic mutations in AML patients with MS, providing insights into the unique characteristics of the mutations and their frequencies. These discoveries are crucial in informing therapeutic and prognostic decisions for individuals with myeloid sarcoma.